2022
DOI: 10.3390/pharmaceutics14040696
|View full text |Cite
|
Sign up to set email alerts
|

Polyenes in Medium Chain Length Polyhydroxyalkanoate (mcl-PHA) Biopolymer Microspheres with Reduced Toxicity and Improved Therapeutic Effect against Candida Infection in Zebrafish Model

Abstract: Immobilizing antifungal polyenes such as nystatin (Nys) and amphotericin B (AmB) into biodegradable formulations is advantageous compared to free drug administration providing sustained release, reduced dosing due to localized targeting and overall reduced systemic drug toxicity. In this study, we encapsulated Nys and AmB in medium chain length polyhydroxyalkanoates (mcl-PHA) microspheres (7–8 µm in diameter). The obtained formulations have been validated for antifungal activity in vitro against a panel of pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
(75 reference statements)
0
10
0
1
Order By: Relevance
“…While free polyenes, notably, amphotericin B, exhibited high toxicity to zebrafish embryos at effective minimum inhibitory concentration doses, this toxicity was not observed when the drugs were loaded into mcl-PHA microspheres. The mcl-PHA/polyene formulations obtained from this study significantly improved the therapeutic profile in zebrafish by increasing the survival rate of infected embryos . Another potential use for PHAs is in creating antimicrobial wound dressings .…”
Section: Toxicity Of Mcl-phasmentioning
confidence: 89%
See 4 more Smart Citations
“…While free polyenes, notably, amphotericin B, exhibited high toxicity to zebrafish embryos at effective minimum inhibitory concentration doses, this toxicity was not observed when the drugs were loaded into mcl-PHA microspheres. The mcl-PHA/polyene formulations obtained from this study significantly improved the therapeutic profile in zebrafish by increasing the survival rate of infected embryos . Another potential use for PHAs is in creating antimicrobial wound dressings .…”
Section: Toxicity Of Mcl-phasmentioning
confidence: 89%
“…The mcl-PHA/polyene formulations obtained from this study significantly improved the therapeutic profile in zebrafish by increasing the survival rate of infected embryos. 110 Another potential use for PHAs is in creating antimicrobial wound dressings. 109 In a study by Balcucho et al, 109 it was found that incorporating poly(3-hydroxyoctanoate)-co-(3hydroxyhexanoate) with silver nanoparticles into wound dressings yielded promising results for treating skin and soft tissue infections associated with chronic skin conditions.…”
Section: ■ Toxicity Of Mcl-phasmentioning
confidence: 99%
See 3 more Smart Citations